Effects of artificial circulation as a lake management tool on profundal macroinvertebrate community - Adoga, Emmanuel (2019)
Artificial circulation as a lake management tool has been widely used to treat eutrophication problem, but its effects on lake ecosystems are still not fully understood. In this study, I examined the impacts of artificial circulation on profundal macroinvertebrate community abundance, diversity and species composition in two lakes, using annual time series data on invertebrates from 2004 to 2017. Moreover, I investigated if the treatment affects the status of profundal macroinvertebrates as an integral component of the ecological status assessment of the studied lakes. In Jyväsjärvi, the artificial circulation was stopped in 2011, whereas in Tuomiojärvi the process was started in 2012. A nearby Lake Alvajärvi served as a control for both treatment lakes, in the Before, After, Control, Impact (BACI) design. Samples were collected in each autumn from two sites in Jyväsjärvi and in one site from each of the other lakes. Stopping the artificial circulation significantly decreased hypolimnetic dissolved oxygen and temperature in Jyväsjärvi, whereas starting the circulation in Tuomiojärvi resulted in opposite changes. Density and biomass of Chironomidae and Oligochaeta generally declined when treatment was stopped in Jyväsjärvi but doubled in Tuomiojärvi after it was started. In both lakes, Chaoboridae abundance was smaller during circulation than during the period without circulation. This could be expected, as chaoborid larvae benefit from the hypoxic profundal as a refugium. Shannon–weaner diversity index values were greater during circulation in both Jyväsjärvi and Tuomiojärvi. In Alvajärvi, no consistent differences in the measured community metrics were observed between the two periods. The results suggest that artificial circulation neither significantly improves nor deteriorates the status of invertebrate communities as it is presently defined and measured according to the Finnish legislation. However, it is important to carry out similar research in other artificially circulated lakes and to consider other biota, to further test the suitability of the management tool for improving lake ecological status.